GONAD DEVELOPMENT OF SANDFISH (Holothuria scabra) FED WITH VITAMIN E-SUPPLEMENTED DIET - Sari Budi Moria Sembiring; Jhon Harianto Hutapea (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2019)
The experiment was conducted to evaluate the effect of vitamin E on the gonad development of sandfish, Holothuria scabra. Four experimental diets were formulated to contain different levels of vitamin E, i.e. 0, 150, 300, and 450 mg/kg diet. Dry diets were prepared at the same protein level (14%). The experiment was arranged in a completely randomized design with four treatments and three replicates. Before the experiment started, the internal organs of broodstock were removed (evisceration) by injecting KCl 1 N reagent into their body, and the gonads were observed to determine the sex of each broodstock. Mean total length and body weight of broodstock after the internal organ removal were 10.95 ± 0.37 cm and 61.12 ± 2.28 g, respectively. Three broodstock (one male and two females) were allocated into each plastic bucket with a volume of 150 L. Each plastic bucket was equipped with aeration and flow-through water system. Broodstock fed with experimental diet once daily at 3% of total biomass for 90 days. The results showed that vitamin E has significant effects on percentage of gonad maturation stages and gonad somatic index (GSI) (P<0.05). Vitamin E at 300 mg/kg diet was the best for gonad maturation of sandfish broodstock. Furthermore, 55.5% and 11.1% of broodstock fed a diet containing 300 mg vitamin E/kg diet reached gonad maturity stage-III and stage-IV, respectively, with GSI of 12.21%.